DRIVING FACTORS OF COMMUNITY INTEREST IN TOURISM IN POST-COVID-19 PANDEMIC IN THE PERSPECTIVE OF HALAL AND CHILD-FRIENDLY FACILITIES, AND INFORMATION TECHNOLOGY - Rana Ardila Rahma; Wala Erpurini; Hani Fitria Rahmani (Jurnal Ekonomi, 2022)
State income fell drastically to Rp. 20.7 billion during the covid-19 pandemic from the tourism and creative economy sectors. Foreign tourists have decreased by 75% or only 25% from usual compared to before Covid-19 (Kemenparekraf), even though tourism is one of the foreign exchange earners that has enormous potential to be developed. This study aims to see public interest in 3 provinces on the island of Java with popular tourist destinations that are influenced by facilities in this case are halal facilities, child-friendly facilities and information technology, which complement the Kamenparekraf program in boosting the interest of local and foreign people in traveling. Currently public interest has not returned to normal due to Covid-19, this research accompanies the Kamenparekraf program in seeing public interest in tourism. The analysis technique in this study is using qualitative data analysis techniques. The sampling method uses cluster sampling which is a sampling technique based on certain clusters. The results of this study prove that each variable partially Halal Facilities and Child Friendly Facilities have a small effect compared to the Information Technology variable on Travel Interest. Meanwhile, if halal facilities, child-friendly facilities, and information technology work well together, it will have a high enough impact on community tourism interest after the COVID-19 pandemic.